HIF drives lipid deposition and cancer in ccRCC via repression of fatty acid metabolism - Weinan Du (Nature Portfolio, 2017)
Clear cell renal cancers (ccRCC) display elevated intracellular lipid storage. Here the authors show that such lipid accumulation is due to the repression of carnitine palmitoyltransferase 1A (CPT1A) enzyme that impairs fatty acid (FA) transport into the mitochondrion resulting in reduced FA beta oxidation.